Community Dedication by KKN UNS Volunteer in Prevention of Covid-19 in Banyumas Regency - Sorja Koesuma (Universitas Sebelas Maret, 2020)
A Clean and Healthy Lifestyle is still a little strange in the people of Banyumas Regency, Central Java. In the midst of the Covid-19 pandemic, PHBS is being intensified because it is one of the efforts to prevent the transmission of the Covid-19 virus. Lack of public understanding and awareness of clean and healthy lifestyle causes them to be indifferent to the current situation. This research was conducted with the aim of providing an understanding of Covid-19, providing an overview of community service activities in the midst of the Covid-19 pandemic, learning assistance at home during the Covid-19 pandemic and providing education to be ready to face the new normal era. This article uses a qualitative descriptive research method. The data collection technique used are (1) Participant observation (2) Interview, to find out the situation through informant(s), (3) Documentation. Some of the activities or projects carried out by the volunteers of KKN Covid-19 Response are Socialization of the Importance of PHBS (Clean and Healthy Behaviour), Assistance of Learning Activities during Covid-19, Education of New Normal Era, and The Effort of Stress Management during Pandemic.